2019
DOI: 10.1016/j.envres.2018.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of prenatal exposure to organic and inorganic contaminants using meconium from an Eastern Canada cohort

Abstract: Evaluating in utero exposure to inorganic and multiclass organic contaminants is critical to better evaluate potential harmful effects on prenatal and postnatal development. The analysis of meconium, the first bowel discharge of the newborn, has been proposed as a non-invasive way to assess cumulative prenatal exposure. The aim of this study was to implement an analytical method for quantifying 72 targeted organic compounds, including pesticides, pharmaceutical compounds and daily life xenobiotics, in meconium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 42 publications
0
27
2
Order By: Relevance
“…Four studies ( Table 6 ) reported on Al in meconium with the mean of means equal to 25 ppm [ 15 , 28 , 30 , 37 ]. All studies except [ 30 ] reported means and standard deviations and all but [ 28 ] used an ICP-MS based analytical method.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies ( Table 6 ) reported on Al in meconium with the mean of means equal to 25 ppm [ 15 , 28 , 30 , 37 ]. All studies except [ 30 ] reported means and standard deviations and all but [ 28 ] used an ICP-MS based analytical method.…”
Section: Resultsmentioning
confidence: 99%
“…Chromium (Cr): Four studies analyzed for Cr [ 15 , 28 , 36 , 37 ]. Study means ranged from 0.03–3.2 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations